Ginsenoside Rb1 ameliorates neutrophil extracellular traps-induced vascular endothelial damage by suppressing apoptosis - Zhang, Biao; Zhao, Junkai; Yin, Jiamin; Chen, Jiaping; Xu, Lingqi (Bangladesh Journal of Pharmacology, 2024)
The study aims to investigate the effect of ginsenoside Rb1 on improving neutrophil extracellular traps-induced vascular endothelial damage. The CCK8 assay was used to evaluate the impact of ginsenoside Rb1 on cell activity. Flow cytometry was used to assess cell apoptosis. E-cadherin was used to determine the damage to endothelial cells, and caspase 3 was used to detect apoptosis-related proteins. Ginsenoside Rb1 (100 μmol/L) could significantly increase the cell viability (p<0.05). At this concentration, the damage caused by neutrophil extracellular traps to human umbilical vein endothelial cells could be reversed (p<0.05). Ginsenoside Rb1 (100 μmol/L) could significantly inhibit the apoptosis and the expression of caspase3 protein caused by neutrophil extracellular traps (p<0.05). Ginsenoside Rb1 can reduce vascular endothelial injury induced by neutrophil extracellular traps, ginsenoside Rb1 protects vascular endothelium by inhibiting cell apoptosis.